Magnetic and gravity anomalies in the Sierra del Padre and Sierra del Tala, San Luis Province, Argentina: evidence of buried mafic-ultramafic rocks - Kostadinoff, Jose (2001)
This paper presents the results of a geophysical study of the southern portion of the Sierra Grande de San Luis, San Luis Province, Argentina. A 26 mGal amplitude Bouguer anomaly 5Charlone anomaly), measuring 40 km long by 7 km wide, between Sierra de los Padres and Zanjitas re ̄ects the presence of high-density rocks located at approximately 2000 m depth. Geophysical models based on more than 300 gravimetric, magnetometric, and geological ®eld measurements and observations suggest that the ma®c±ultrama®c belt of Sierra Grande de San Luis continues south of San Luis. The low magnitude of the terrestrial magnetic ®eld anomalies indicates that these ma®c±ultrama®c rocks do not carry a base metal sul®des 5BMS) mineralization. The Charlone gravimetric anomaly is generated by a belt of ma®c± ultrama®c rocks whose amplitude is comparable with that responsible for the Virorco-Las Aguilas gravimetric anomaly.